Spina Bifida Occulta in an Adult Presenting as Perilesional Hemorrhage - Amit Agrawal; Vissa Santhi; Ranjan Kumar Jena; Umamaheswara Reddy V; Yashwant Sandeep (Indian Journal of Neurosurgery)
Occult spinal dysraphism with spinal lipoma, is a rare congenital spinal dysraphic anomaly which usually involves lumbosacral region and manifests in childhood. In the present article, we discuss a case of a 26-year-old man who developed sudden low back pain following intercourse. Magnetic resonance imaging of the lumbosacral spine was suggestive of spina bifida occulta with hemorrhage. The patient underwent a L4–5 laminectomy in the emergency. There was the presence of altered blood in the vicinity of the lesion suggestive of recent hemorrhage. Histopathological examination of the lesion was suggestive of the lipoma. In the present case, the patient had occult spina bifida due to lumbosacral lipoma leading to the tethering of the dura. Strenuous activity resulted in overstretching of the tethered structures and subsequent hemorrhage and intense low back pain which responded well to the surgical treatment.